Transformational leadership on work engagement: The mediating role of work-life balance - Hendro Setyono; Wiwiek Rabiatul Adawiyah; Syifa Fitriani (Universitas Ahmad Dahlan, 2024)
Implementing a suitable leadership style can increase work engagement. Work-life balance is necessary to support transformational leadership in improving work engagement. This study examines how transformational leadership affects work engagement, using work-life balance as a mediating factor. 44 respondents represent the study's sample, and the population focus is Yogyakarta Industry and Trade Agency employees. The study's findings show that transformational leadership positively influences work engagement. Work-life balance is positively influenced by transformational leadership. Work engagement is positively influenced by work-life balance. Transformational leadership and work engagement are mediated by work-life balance.